2011
DOI: 10.1007/s00421-011-2204-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy strength training on muscle thickness, strength, jump performance, and endurance performance in well-trained Nordic Combined athletes

Abstract: The purpose of the present study was to investigate the effect of supplemental heavy strength training on muscle thickness and determinants of performance in well-trained Nordic Combined athletes. Seventeen well-trained Nordic Combined athletes were assigned to either usual training supplemented with heavy strength training (STR; n = 8) or to usual training without heavy strength training (CON; n = 9). The strength training performed by STR consisted of one lower-body exercise and two upper-body exercises [3-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 56 publications
10
50
3
1
Order By: Relevance
“…These findings correspond with other studies that have found simultaneous improvements of maximal strength and sprint abilities following training programs including exercises such as bench press and dumbbell bench pull in kayaking (Liow & Hopkins, 2003) and in wheelchair racing (Turbanski & Schmidtbleicher, 2010). The present improvements in 1RM are slightly lower than the 10% increase in 1RM in a double poling exercise after 12 weeks of heavy strength training in highly trained cross-country skiers (Losnegard et al, 2011), and much lower than the 19-23% improvement after 9-12 weeks heavy strength training in cross country skiers and nordic combined athletes (Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012). The differences in strength gains between studies can probably be explained by a smaller strength gain potential in the already highly trained upper-body muscles of the elite ice sledge hockey players examined here and a shorter strength training period than in the previous studies.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These findings correspond with other studies that have found simultaneous improvements of maximal strength and sprint abilities following training programs including exercises such as bench press and dumbbell bench pull in kayaking (Liow & Hopkins, 2003) and in wheelchair racing (Turbanski & Schmidtbleicher, 2010). The present improvements in 1RM are slightly lower than the 10% increase in 1RM in a double poling exercise after 12 weeks of heavy strength training in highly trained cross-country skiers (Losnegard et al, 2011), and much lower than the 19-23% improvement after 9-12 weeks heavy strength training in cross country skiers and nordic combined athletes (Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012). The differences in strength gains between studies can probably be explained by a smaller strength gain potential in the already highly trained upper-body muscles of the elite ice sledge hockey players examined here and a shorter strength training period than in the previous studies.…”
Section: Discussioncontrasting
confidence: 58%
“…Associations between upper-body strength and various types of performances are further supported by studies on elite kayakers (Liow & Hopkins, 2003;Uali et al, 2012), wheelchair racers (Turbanski & Schmidtbleicher, 2010), surfers (Sheppard et al, 2012) and luge athletes (Crossland, Hartman, Kilgore, Hartman, & Kaus, 2011;Platzer, Raschner, & Patterson, 2009). A few of these studies also showed simultaneous improvements of maximal strength and sprint abilities with heavy upper-body strength training (Liow & Hopkins, 2003;Turbanski & Schmidtbleicher, 2010), whereas such training in cross-country skiers improved upper-body strength, skiing economy and endurance performance (Hoff, Gran, & Helgerud, 2002;Losnegard et al, 2011;Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012). Whether these strength training effects apply for elite athletes who are specialized in an isolated upper-body movement needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies clearly shows the effectiveness of strength training aiming at specifically increasing maximal force capabilities (Cormie et al, 2007, 2010; Rønnestad et al, 2012, 2016; Zaras et al, 2013). They have shown improvements in maximal strength parameters (e.g., 1RM, 1RM/BM ratio) through trainings involving the use of high loads (>70% RM), in order to achieve the maximal neuromuscular adaptations, in periods ranging from 6 to 12 weeks.…”
Section: Introductionmentioning
confidence: 88%
“…Some traditional training methods have been considered for power improvement, such as: power and ballistic training (e.g., Wilson et al, 1993; Newton et al, 1996; Cormie et al, 2007, 2010; Argus et al, 2011; Markovic et al, 2011; Sheppard et al, 2011; Zaras et al, 2013), heavy-load training (focusing more on strength; e.g., Gorostiaga et al, 1999; Harris et al, 2000; Chelly et al, 2009; Rønnestad et al, 2012, 2016) and combined training (strength-power training; e.g., Wilson et al, 1993; McBride et al, 2002; Kotzamanidis et al, 2005; Cormie et al, 2007, 2010; Smilios et al, 2013; Zaras et al, 2013). This kind of global power training prescription similar for all athletes resulted in contrasting findings as to the effects on jumping performance (e.g., Wilson et al, 1993; Gorostiaga et al, 1999; Harris et al, 2000; McBride et al, 2002; Kotzamanidis et al, 2005; Cormie et al, 2007, 2010; Chelly et al, 2009; Rønnestad et al, 2012, 2016; Smilios et al, 2013; Zaras et al, 2013), likely because of the various levels and F-v characteristics of the populations tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation